The Influence of Face Consciousness on Brand Consumption of Apparel Products in Urban Areas of China - WEI, ZHENG (2008)
This dissertation mainly aims at making a deep exploration of how face consciousness specifically impacts on the consumption of apparel products with known brand names among young female consumers living in China's urban areas. 15 young ladies, aging in the range between 21 and 25 from several main urban cities in China, i.e. Beijing, Shanghai, Xiamen, Qingdao and Changchun, were interviewed, providing insights into the correlation between their concern of face and their specific consumption behaviors. The study figured out two patterns of face consciousness from the findings. One is actually a normal sense of social self-values that consumers hope others to associate to them during particular contacts. Accordingly, consumers are inclined to choose clothes with named brands as long as they can afford them because they believe dressing themselves in branded clothes is positively correlated to establishing and enhancing their self-images in public occasions; in other words, it can enhance their faces. However, if they can not afford, they will not be upset either. Furthermore, for them, pursuing the named brand blind will be considered to do harm to the face. The other pattern, however, refers to excessive vanity. Then, the consumption of branded clothes with this pattern is merely for the purpose of showing off or making comparison with others.